The Term ‘Ebda’ in the Comparative View of Fakhr Razi and Allameh Tabatabai - Mohammad Bahrami (Comparative Theology)
The term Ebda (innovation) as one of God’s attributes has attracted the attention of a group of philosophers, theologians, and Quranic commentators, while others have shown less interest in it. Among the Quranic commentators, Fakhr al-Din al-Razi and Allameh Tabatabai have given special attention to the term Ebda, considering it one of God’s actual attributes and deeming its application to contingent beings incorrect. They identify creation, lack of precedent, timelessness, placelessness, and instantaneous realization as components of Ebda. They do not view Ebda as merely a term and provide rational and narrative reasons to prove its instantaneous nature. Allameh and Fakhr Razi differ in their views on the distinction between Ebda and creation (Khalg), Ebda and origination (Ijad), and Ebda and invention (Ekhtera). The main objective of this research is to uncover Fakhr Razi and Allameh’s perspectives on the term Ebda and their differences and similarities. The aim of this study is to compare their views on the term Ebda and to pave the way for organizing Imami and Ashari terminology based on conceptual relationships, facilitating transfer and education, simplifying translation, indexing, and categorizing God’s attributes. This study adopts a descriptive-analytical method and a library-based approach. In this method, the term Ebda is explained, its similarities and differences with other terms are examined, and its components are stated. Keywords: Fakhr Razi, Allameh Tabatabai, Innovation (Ebda), Invention (Ekhtera), Creation (Khalg), Development. IntroductionIn human knowledge, certain terms acquire specialized meanings, forming a system of concepts. Theology and philosophy, like other sciences, contain a set of terms intertwined with their understanding. The ambiguity in understanding one side leads to ambiguity in the other, complicating the compilation, dissemination, translation, summarization, storage, and organization of theological and philosophical texts.Ebda is a Quranic and narrative term rooted in Bada and appears in various forms in the Quran and Hadith. The use of the term Ebda and its derivatives in the verses of revelation and narrations has necessitated a terminology of Ebda by some commentators, philosophers, and theologians. Some offer a broad definition with several conditions for Ebda, while others provide a minimal definition, identifying the lack of precedent as its sole criterion. Some see Ebda as approximately synonymous with creation, formation, invention, etc., while others do not accept this equivalence. Fakhr Razi and Allameh Tabatabai have pursued the terminology of Ebda and integrated philosophical, theological, and exegetical perspectives. This research examines their views on Ebda, highlighting their similarities and differences, and identifies shortcomings in each of their approaches. Materials and MethodsThe methodology of this research is descriptive-analytical and library-based. This study explains the term Ebda, examines its similarities and differences with other approximate synonyms and presents the characteristics of Ebda. The research aims to explore Allameh Tabatabai and Fakhr Razi’s perspectives on the term Ebda in light of their philosophical, theological, and exegetical works. Research FindingsThe findings of this research are summarized as follows:Evidence Utilization: Allameh Tabatabai uses both rational and narrative evidence to support the concept of Ebda, while Fakhr al-Din al-Razi mainly relies on Quranic verses.Scope of Ebda: Allameh Tabatabai believes that all creations, including human actions and relationships between objects, are forms of Ebda. He holds that all beings are Badi (created without precedent), whereas Fakhr Razi emphasizes the non-material aspects of entities.Attributes and Will: Both Allameh Tabatabai and Fakhr Razi agree that Ebda depends on God’s will, but they differ on whether Ebda pertains exclusively to non-material entities or includes all creation.Theological and Philosophical Synthesis: Despite methodological differences, both scholars significantly contribute to the theological and philosophical understanding of Ebda, bridging gaps between philosophical, theological, and exegetical perspectives. Discussion of Results and ConclusionThis study investigates the perspectives of Fakhr al-Din al-Razi and Allameh Tabatabai on the term Ebda. The research questions focus on identifying their views on the concept, examining the similarities and differences, and understanding the implications of these perspectives in theological and philosophical contexts. The hypotheses suggest that both scholars see Ebda as a unique attribute of God, distinct from other forms of creation.The findings confirm that both al-Razi and Tabatabai consider Ebda an act of God without precedent, supported by rational and scriptural evidence. However, they diverge in their methodologies: al-Razi predominantly uses Quranic verses, while Tabatabai incorporates both rational and scriptural proofs. Additionally, while al-Razi emphasizes the non-material aspects of creation, Tabatabai extends Ebda to all creations, including human actions.The study reveals a shared understanding of Ebda as dependent on God’s will, reflecting a common theological stance. Despite methodological differences, both scholars significantly contribute to the theological and philosophical understanding of Ebda, aiding in bridging gaps between various schools of thought.In conclusion, the research highlights the need for a systematic approach to categorizing and interpreting divine attributes, emphasizing the importance of integrating philosophical, theological, and exegetical perspectives to enhance the comprehension and teaching of Islamic theology.